THE EFFECT OF SOCIAL MEDIA INFLUENCERS ON THE INTEREST OF BUYING AUDIENCES ON FOOD AND BEVERAGE PRODUCTS IN JABODETABEK AREA - Rendy Muljana; Oscar Jayanegara (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The study aimed to analyze influencer profile factors that influence the level of trust in influencers, as well as the level of trust in influencers affecting audience buying interests. Researchers use a quantitative approach with structured questionnaire survey methods. The sampling technique in this study is non probability sampling. The sample in this study was selected using purposive sampling techniques with a sample count of 200 that used the Slovin formula to determine the number of samples. Based on the results of the analysis, it can be concluded that the influencer popularity variable affects trust in influencers, influencer credibility affects trust in influencers, trust in influencers affects the interest in buying audiences, while influencer popularity and influencer credibility simultaneously affect trust in influencers.